Adopting the Blue Green Economy Term to Achieve SDGs in Digital Learning: Opportunities and Challenges for Indonesia - Sungkawati, Endang; Uthman, Yusuf Olawale Owa-Onire (CV. Bimbingan Belajar Assyfa, 2024)
This study examines the adoption of the